Perceptions of Artificial Intelligence Among IT Professionals: Exploring Job Opportunities, Threats, and the Moderating Role of Technology Literacy - Khadka, Sajita; Kunwar, Sanjeev; Gautam, Roshni; Poudel, Santosh; Khadka, Sijan; Manandhar, Rashil; Mahat, Dipak (International Journal of Education, Management, and Technology, 2025)
Artificial Intelligence (AI) is transforming industries worldwide, creating both opportunities and challenges for IT professionals. This study examines the perceptions of AI among IT professionals in Kathmandu, focusing on job opportunities, threats, and the moderating role of Technology Literacy (TL). The research adopts a descriptive and causal-comparative design within the positivist paradigm, emphasizing measurable and objective data. A structured questionnaire with a 5-point Likert scale was distributed via Google Forms to 128 IT professionals in Kathmandu. Descriptive statistics indicated that IT professionals generally have a moderate level of Technology Literacy (mean scores ranging from 2.39 to 2.78). AI was perceived favorably, with mean scores between 3.02 and 3.39. However, perceived threats from AI were moderate (mean scores from 2.33 to 2.60), suggesting concerns about job security. Perceived opportunities were also moderate (mean scores between 2.38 and 2.81), indicating a balanced view of AI’s potential benefits and risks. Correlation and regression analyses revealed that Technology Literacy significantly moderates the relationship between AI and job opportunities, as well as AI and threats, suggesting that higher TL mitigates fears and enhances positive perceptions of AI. The study highlights the dual impact of AI on IT professionals, with both opportunities and threats being perceived at moderate levels. Technology Literacy plays a crucial role in shaping these perceptions, underscoring the need for continuous learning and adaptation in the IT sector.